ANGPTL4 Expression in Ovarian Granulosa Cells Is Associated With Polycystic Ovary Syndrome - Jiang, Qi; Pan, Ye; Li, Ping; Zheng, Yanjun; Bian, Yuehong; Wang, Wenqi; Wu, Guihua; Song, Tian; Shi, Yuhua (Frontiers in Endocrinology, 2022)
Objectives This study aims to characterize the expression of ANGPTL4 in ovarian granulosa cells (GCs) and its association with polycystic ovary syndrome (PCOS). Methods This study included 104 PCOS patients and 112 women in control group undergoing in vitro fertilization-embryo transfer (IVF-ET) from the reproductive hospital affiliated with Shandong University from 2019 to 2021. By reverse transcription and real-time quantitative (RT-q) PCR, the mRNA expression of ANGPTL4 in GCs was assessed, and clinical information for these patients were then reviewed and analyzed. Results The RT-qPCR results showed that ANGPTL4 expression in the control group was significantly lower than that in the PCOS group (p = 0.000) and had positive association with AMH (r = 0.211), HOMA-IR (r = 0.174), LDL/HDL (r = 0.176), ApoB/ApoAI (r = 0.155), and TC/HDL (r = 0.189). Additionally, the high expression of ANGPTL4 in the ovarian granulosa cells might be an independent predictor in PCOS (OR: 3.345; 95% CI: 1.951–5.734) with a close contact with incidence of PCOS (AUC: 0.704; 95% CI: 0.633–0.774, p < 0.001). Conclusions Our study revealed higher ANGPTL4 expression in ovarian GCs with PCOS. Its association with glucose and lipid metabolism showed that ANGPTL4 might play an important role in PCOS metabolism and pathogenesis.